Dynamics of metatranscription in the inflammatory bowel disease gut microbiome - Schirmer, Melanie (Nat Microbiol, 2018)
Inflammatory bowel disease (IBD) is a group of chronic diseases of the digestive tract affecting millions of people worldwide. Genetic, environmental and microbial factors have been implicated in onset and exacerbation of IBD. However, the mechanisms associating gut microbial dysbioses and aberrant immune responses remain largely unknown. The integrative Human Microbiome Project (iHMP) seeks to close these gaps by examining the dynamics of microbiome functionality in disease by profiling the gut microbiomes of more than 100 individuals sampled over a one year period. Here, we present the first results based on 78 paired fecal metagenomes/metatranscriptomes and 222 additional metagenomes from 59 Crohn’s disease (CD), 34 ulcerative colitis (UC), and 24 non-IBD control patients. We demonstrate several cases in which measures of microbial gene expression in the inflamed gut can be informative relative to metagenomic profiles of functional potential. First, while many microbial organisms exhibited concordant DNA and RNA abundances, we also detected species-specific biases in transcriptional activity, revealing predominant transcription of pathways by individual microbes per host (e.g. by Faecalibacterium prausnitzii). Therefore, a loss of these organisms in disease may have more far-reaching consequences than suggested by their genomic abundances. Further, we identified organisms that were metagenomically abundant but inactive or dormant in the gut with little or no expression (e.g. Dialister invisus). Lastly, certain disease-specific microbial characteristics were more pronounced or only detectable at the transcript level, such as pathways predominantly expressed by different organisms in IBD patients (e.g. Bacteroides vulgatus and Alistipes putredinis). This provides potential insights into gut microbial pathway transcription that can vary over time, inducing phenotypic changes complementary to those linked to metagenomic abundances. The study’s results highlight the strength of analyzing both the activity and presence of gut microbes to provide insight into the role of the microbiome in IBD.